2003
DOI: 10.2320/matertrans.44.2605
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Perpendicular Magnetic Anisotropy in Tb-Fe Amorphous Alloy

Abstract: The origin of perpendicular magnetic anisotropy has been investigated in a thick Tb-Fe amorphous alloy plate prepared by dc high-rate sputtering. In the as-prepared samples with and without a Cu substrate, no distinct difference in perpendicular magnetic anisotropy was confirmed. After annealing, the perpendicular magnetic anisotropy in the sample with a Cu substrate was maintained, whereas that disappeared in the sample without a Cu substrate. Inducing thermal strains with an epoxy resin, the perpendicular ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
(34 reference statements)
2
4
0
1
Order By: Relevance
“…These structural changes are probably linked to the strains induced in the alloy during film growth and their release with the temperature, possibly favored by their interplay with the magnetoelastic properties of each of the magnetic environments. The importance of anelastic strains in the development of the magnetic anisotropy of these alloys is well known [11,68,69]. In fact, we have observed an irreversible reduction of about 20% in the magnetic anisotropy of our films with annealing temperatures of only 400 K [41].…”
Section: Variation Of the Measured Neodymium Magnetic Momentmentioning
confidence: 55%
“…These structural changes are probably linked to the strains induced in the alloy during film growth and their release with the temperature, possibly favored by their interplay with the magnetoelastic properties of each of the magnetic environments. The importance of anelastic strains in the development of the magnetic anisotropy of these alloys is well known [11,68,69]. In fact, we have observed an irreversible reduction of about 20% in the magnetic anisotropy of our films with annealing temperatures of only 400 K [41].…”
Section: Variation Of the Measured Neodymium Magnetic Momentmentioning
confidence: 55%
“…In this regard, a lot of effort has been made to investigate the intrinsic magnetic properties over a wide composition as well as temperature range, and how they are influenced by the growth conditions, like sputtering pressure (Jiang et al, 2010), substrate choice (Na et al, 2003), substrate bias voltage (Alperin et al, 1975), or external strain (Ohta et al, 2003). These research activities were encouraged by improved preparation techniques, which allowed preparing thin films in the thickness range of only some nanometers at reproducible high quality.…”
Section: Hebler Et Al Ferrimagnetic Tb-fe Alloy Thin Filmsmentioning
confidence: 99%
“…Thin films of an amorphous RE-TM ferrimagnet have been often reported to exhibit PMA, possibly from the interfacial strain on the ferrimagnetic layer involving multiple mechanisms associated with magnetostriction, [36] dipolar effects, [37] and anisotropic atomic-pairs correlations. [38][39][40] In addition, the MA of the ferrimagnetic layer was found to be sensitive to the growth conditions (e.g., growth of the layer under external strain [41] and the presence of Ta underlayer [22] ) as well as the post-annealing procedures. [42] Ueda et al [22] reported that the threshold thickness of the RE-TM ferrimagnetic layer for the transition of MA from IMA to PMA can vary depending on the existence of the Ta underlayer.…”
Section: Tma In Gd/co Multilayers For In-plane Symmetry Breakingmentioning
confidence: 99%